The Existence of Women in the Traditional Rituals of the Jatilawang Bonokeling Community in Banyumas Regency - Arauf, Muta Ali (International Journal of Social Science and Religion (IJSSR), 2023)
This research aims to explore the existence of women in the procession of perlon unggahan ritual, one of rituals in Bonokeling indigenous community. This research uses qualitative method with empirical or field research approach. Data collection methods were conducted by means of in-depth interviews, observations, documentations and literature studies. The results obtained indicated that women have a good role and position in the Bonokeling community. This happens because of the awareness of gender equality in Bonokeling community as a representation of egalitarian character. In traditional ceremonies in Bonokeling community, women have productive, reproductive, and socio-cultural roles. Women's interests in perlon unggahan rituals can be involved and carry out worship. For the Bonokeling community or breed, perlon unggahan has a very sacred value and becomes a spiritual path (worship charity). Women as nyai wadon kunci and so on (organizational structure of nyai wadon kunci), nyai wadon bedogol, and so on (organizational structure of nyai wadon bedogol). Their roles include (a) Nyai wadon kunci assisting the task of kyai kunci; (b) nyai wadon bedogol assisting the task of kyai bedogol; (c) women: carrying out tasks in the perlon unggahan’s tradition as specified.Keywords: women's existence, perlon unggahan ritual, Bonokeling community